2017
DOI: 10.1017/s1751731116002111
|View full text |Cite
|
Sign up to set email alerts
|

Ability of dairy cows to be inseminated according to breed and genetic merit for production traits under contrasting pasture-based feeding systems

Abstract: Strong genetic selection on production traits is considered to be responsible for the declined ability of dairy cows to ensure reproduction. The present study aimed to quantify the effect of genetic characteristics (breeds and genetic merit for production traits) and feeding systems (FS) on the ability of dairy cows to be inseminated. An experiment was conducted during 9 years on Normande and Holstein cows assigned to contrasted pasture-based FS. Diets were based on maize silage in winter and grazing plus conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Holstein cows in the content group and under the low FS showed the lowest conception rate (38% at 42 d and 66% by the end of the breeding season). This is not consistent with their submission rate (63% at 21 d; Bedere et al, 2016b), and the present study showed they had a higher proportion of NF/EEM than other groups (47% at first and second services the range was from 19 to 29% for other groups). Holstein cows had the lowest BCS at calving, at nadir, at first and second service, and at the end of lactation.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Holstein cows in the content group and under the low FS showed the lowest conception rate (38% at 42 d and 66% by the end of the breeding season). This is not consistent with their submission rate (63% at 21 d; Bedere et al, 2016b), and the present study showed they had a higher proportion of NF/EEM than other groups (47% at first and second services the range was from 19 to 29% for other groups). Holstein cows had the lowest BCS at calving, at nadir, at first and second service, and at the end of lactation.…”
contrasting
confidence: 99%
“…Other results also showed that Holstein cows in the milk group had the lowest submission in both FS (Bedere et al, 2016b). Their ability to be pregnant at second service balanced this result so that their recalving rate (56%) is not different from Holstein cows in the milk group under the low FS (54%) and Holstein cows in the content group under high FS (53%).…”
mentioning
confidence: 76%
“…Much of those protestations 'fell on deaf ears' because it was largely regarded that breeding for or against fertility traits was not possible due to its low heritability (Berry et al, 2014). Numerous experiments were undertaken in New Zealand (Kolver et al, 2002;Roche et al, 2006a;Macdonald et al, 2008b), Australia (Fulkerson et al, 2001 and2008), France (Bedere et al, 2015(Bedere et al, , 2016(Bedere et al, , 2017a(Bedere et al, and 2017b and Ireland (Buckley et al, 2000;Kennedy et al, 2002;Horan et al, 2005a) to determine if different genetic strains performed differently under different feeding systems, in a holistic or overall economic sense. Although there was evidence that feeding regimen influenced the marginal milk production response to non-pasture feed and the ability of the dairy cow to exhibit her genetic potential, compared with her peers (Kennedy et al, 2002;Fulkerson et al, 2008), the greatest differences between the strains were in the extent of their negative energy balance in early lactation (Buckley et al, 2000;Roche et al, 2006a;McCarthy et al, 2007) and in their pregnancy rates in a seasonal calving system (Horan et al, 2005c;Macdonald et al, 2008b;Bedere et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…The dairy cow situation is more complicated as a consequence of the high nutrient demand for lactation in this period (Friggens et al, 2010) and impacts on a range of fertility characteristics. To obtain good reproductive performance, luteal activity has to be restored and regular, oestrus and heats should be well expressed and easy to detect, and after artificial insemination (AI), fertilisation should be effective and the embryo implantation successful to re-calve (Bedere et al, 2017a(Bedere et al, , 2017b. Although evidence of genotype × environment interaction is scarce (Washburn & Mullen, 2014), evidence by O' Sullivan et al, (2019aSullivan et al, ( , 2019b and Horan et al (2004) suggests that sustainable genetic improvement is contingent on compatibility with the system in which the genetics is expected to perform.…”
Section: Ability To Reproduce and Achieve Compact Parturitionmentioning
confidence: 99%